Isolation and optimization of cellulase producing bacteria from Hon Giao pygmy forest soil in Vietnam - T. T. A. Le (Brazilian Journal of Biology)
Abstract The cellulase producing bacteria were isolated from the soil of a pygmy forest in Vietnam. Out of 13 cellulase producing isolates, two strains exhibited the maximum clearance zone and cellulase producing capacity and were identified as Bacillus sp. D2T3-7 and Bacillus velezensis strain D3T1-18 based on morphological; cultural, biochemical and phylogenetic analysis of 16S rRNA. The optimal culture conditions including pH, temperature, carbon sources, and nitrogen sources for cellulase activity were investigated. The maximal cellulase activity were obtained at pH of 5.5 of incubation at 35oC with carboxymethyl cellulase as the sole carbon source, and ammonium sulfate as sole nitrogen source for both isolates. The results of the study suggest bacteria isolated from pigmy forests have the potential for degradation of cellulose rich pollutants in different environmental matrices such as agricultural waste, paper sludge, textile fibers.